Elastic properties of borotellurite glass doped with manganese oxide - Syed Hashim, Syed Putra Haizam (2016)
Now a day, glass had played very important role in our society. Various types of glasses with certain composition had been prepared for specific application. Even though preparation of glass basically for the purpose of application, in this research, only certain of the glass properties will be studied to analyse the tendency or the ability of prepared glass for further research in glass radiation sensor. Boro-tellurite glasses with the dopant of manganese ion were synthesis in this study by using melt and quench technique. Two series of [(B2O3)0.3(TeO2)0.7](100-x) (MnO)x with percentage of mole x from 0.1 to 0.4 glass had been successfully prepared to find the optimum percentage of amount of manganese ions needed so that the glass structure become fully amorphous. Then another four series of [(B2O3)0.15 (TeO2)0.85](100-x)(Mn2O3)x with percentage of mole x from 1 to 5 glass had also successfully prepared. Samples prepared tested for X-ray diffraction technique. Result shows one sharp peak occurs for the percentage of mole at x = 0.1 and 0.2 for the first series of glass. However, the peak disappear at x= 0.3 and 0.4. For all other prepared samples, there were no peaks at all shows that the glasses have entered completely in amorphous structure. The densities of prepared sample were then determined by using the Archemedes’s principle and the molar volume of the sample calculated. Structural bonding between the glasses molecules were analysed by using FT-IR spectrum. Then, by using ultrasonic MBS8000, longitudinal and transverse wave velocity had been determined. From the data of the density and the ultrasonic velocities, elastic properties of these glasses then obtained. Young’s modulus, bulk’s modulus and debye temperature of these borotellurite doped glass were found to be decrease with the increasing of manganese ions inside the glass network even after the glass were remelt. All series of glasses were found to have a decrease elastic modulus with temperature. All the trend were finally compared with Rocherulle’s model and observed the same trend for all elastic velocities and elastic moduli. After remelting process, it was observed that the glass structure become more open and less strong.